Níveis de caroço de algodão em dietas contendo silagem de cana-de açúcar - Gesiane Moura Neves Reboucas (2012)
The aim of this study was to evaluate the nutritional characteristics of silage cane sugar with inclusion of urea and 1% levels of cottonseed (CS) (0%, 5%, 10% and 15%) in diets for ruminants, observing the effect on the intake and digestibility of nutrients, energy metabolism, methane production, performance and ingestive behavior. In experiment 1 were determined intake and digestibility of nutrients and ingestive behavior of sheep. The digestibility of dry matter (DM), organic matter (OM), ether extract (EE), total digestible nutrients (TDN), neutral detergent fiber (NDF), acid detergent fiber (ADF) and crude protein (CP) does not were affected (P> 0.05). The inclusion of CA affected (P <0.05) digestibility of non-fiber carbohydrates (DNFC). The intake of nitrogen (N ingested), its uptake (N uptake) and retention (N retention) were not affected (P> 0.05). The relationship Nret / Ning, was influenced (P <0.05) by the dietary inclusion of CA. Among the activities of feeding, only the time devoted to leisure (TL) was not affected (P> 0.05) by treatments. The efficiencies feed (EF) and rumination (ER) were not affected (P> 0.05). In experiment 2, the objective was to evaluate the inclusion of CA in diets based on silage cane sugar in sheep feeding on energy metabolism and the production of methane. The gross energy consumed (GEC), digestible energy (DEC), metabolizable energy (MEC) and net energy (NEC) were influenced (P <0.05). The loss of urine, feces, methane and increase caloric not influenced by increasing levels of CA (P> .05), however, the loss of gross energy in faeces and its relation to gross energy consumed was affected (P < 0.05). The apparent digestibility of gross energy (DEG) was influenced (P <0.05), as well as the metabolizable energy for maintenance (Km) and the ratio of net energy and gross energy consumed (NE / GE%). The daily gas exchange (O2 consumption, CO2 and CH4 production), in liters per unit of metabolic size (L / UMS), heat production (HP) and respiratory quotient (RC) were not influenced by diet (P> 0.05). In experiment 3 were evaluated inclusion levels of CA and its effects on consumption and nutrient digestibility, milk production and composition. The intake of acid detergent fiber (IADF), non-fiber carbohydrates (INFC) and ether extract (IEE) were influenced by the inclusion of CA. The study showed quadratic regression for the IADF, and the IEE and INFC, linear effects downstream and upstream, respectively. The digestibility of dry matter (DDM) and organic matter (DOM) were not affected (P 0.05) by experimental treatments. The digestibility of crude protein (DCP) was influenced (P 0.05) for inclusion in the diets of CS. There was no effect (P 0.05) the inclusion of cottonseed on digestibility of fibrous fractions. The inclusion of increasing levels of CS did not affect (P 0.05) most of the components of milk, including milk yield (kg / day), except for the dried extracts total (DET) and defatted (DED) ( P 0.05), both showing a quadratic effect in the regression analysis. The average milk production was 14.31 kg / day.